Morphology of Anterolateral Ligament of the Knee: A Cadaveric Observation with Clinical Insight - Potu, Bhagath Kumar (Adv Med, 2016)
Background. The morphology and function of anterolateral ligament (ALL) of the knee are not clearly understood even today with all the sophisticated techniques available. There have been differing descriptions of the ALL of the knee in literature, and not all of them have been named or described clearly. Aim. The present study was undertaken to provide a clear structure/relationship description on ALL. Materials and Methods. We used 24 formalin-fixed cadaveric limbs. Knee regions of the all the limbs were neatly dissected and the ALL was exposed. Its proximal and distal attachments were traced carefully. Middle portion of ALL was removed and processed for histological analysis. Results. ALL was found in one right knee (4.16%). It extended distally from the lateral femoral condyle to the lateral tibial plateau margin. Its attachment on the tibial plateau was located between head of the fibula and Gerdy's tubercle. A strong connection was identified between the ALL and the periphery of the middle third of the lateral meniscus. Histological analysis of ALL confirmed the presence of true ligamentous structure in it with dense connective tissue and plenty of fibroblasts. Conclusion. The prevalence of ALL in different populations along with its clinical significance has been discussed in detail in this paper.